The effect of both microeconomic and macroeconomic determinants on cash holdings: Evidence from US listed firms - Wu, Tianhao (2016)
The market begin to be aware of the important impacts of corporate liquidity as crucial strategies for companies. There are a number of studies including empirical evidence from different samples based on the effect of firm characteristics on the cash level of firms. However, few literatures focus on the effect of macroeconomic determinants. The objective of this study is to check the effects of firm characteristics in the models considering macroeconomic conditions and to investigate the impacts of macroeconomic determinants. The empirical analysis is conducted based on a sample consists of data of US listed companies from 2004 to 2015. The econometric techniques applied in this study include pooled OLS model and fix effects model followed by robustness test. According to the results, effect of most of the firm characteristics is consistent with previous studies and theories. Furthermore, macroeconomic determinants including interest rate and inflation show significant impacts on corporate cash holdings.